Thyroid Metastases from Renal Cell Carcinoma: Review of the Literature - Alessandro Sindoni; Massimo Rizzo; Giovanni Tuccari; Antonio Ieni; Valeria Barresi; Letterio Calbo; Eugenio Cucinotta; Francesco Trimarchi; Salvatore Benvenga (The Scientific World Journal)
The thyroid gland is a rare site of clinically detectable tumor metastasis and kidneys are frequently the site of the parent malignancy. In the present review on thyroid metastases from renal cell carcinoma, cases were searched on PubMed by entering the strings: “renal carcinoma [or“hypernephroma”] AND thyroid metastasis/metastases”. Thus, we retrieved a total of 111 cases that were published between 1964 and 2007, a total that became 113 by adding two patients observed by us. The female to male ratio was 1.35:1. The primary renal cancer was almost always unilateral (90%) (with no significant side preference) and only rarely bilateral (9% in men, 4% in women), whereas bilaterality of thyroid metastases was relatively more frequent (28%). Thyroid metastasis from renal cancer was commonly single with a unique node that appears solid and hypoechoic at ultrasonography, approximately 9 years after nephrectomy. Concordance of lateralization was insignificantly greater for the right kidney/right thyroid lobe pattern (54%) than for the left kidney/left thyroid lobe pattern (40%), regardless of gender. Finally, survival was longer for women. Thyroid metastases, even if rare in the clinical practice, must be considered in the differential diagnosis of a thyroid nodule, particularly in patients who have a history of malignancies.